Induction of Cell Activation Processes by Low Frequency Electromagnetic Fields - Myrtill Simkó (The Scientific World Journal)
Electromagnetic fields (EMF) such as those from electric power transmission and distribution lines (50/60 Hz) have been associated with increased risk of childhood leukemia, cancer of the nervous system, and lymphomas. Several in vitro studies on EMF effects were performed to clarify the existing controversies, define the risks, and determine the possible mechanisms of adverse effects. In some of these reports, the effects were related to other mechanisms of carcinogenesis. Modification in cell proliferation was observed after EMF exposure and a few reports on cytotoxic effects have also been published. This limited review gives an overview of the current results of scientific research regarding in vitro studies on the effects of power line frequency EMF, but also cell biological mechanisms and their potential involvement in genotoxicity and cytotoxicity are discussed. Cell cycle control and signal transduction processes are included to elucidate the biochemical background of possible interactions. Exposure to EMF has been also linked to the incidence of leukemia and other tumors in some epidemiological studies and is considered as “possibly carcinogenic to humans”, but there is no well-established biological mechanism that explains such a relation. Furthermore, EMF is also shown as a stimulus for immune relevant cells (e.g., macrophages) to release free radicals. It is known that chronic activation of macrophages is associated with the onset of phagocytosis and leads to increased formation of reactive oxygen species, which themselves may cause DNA damage and are suggested to lead to carcinogenesis. To demonstrate a possible interaction between EMF and cellular systems, we present a mechanistic model describing cell activation as a major importance for cellular response.